Cortical thickness differences between bipolar depression and major depressive disorder. (16th January 2014) - Lan, Martin J; Chhetry, Binod Thapa; Oquendo, Maria A; Sublette, M Elizabeth; Sullivan, Gregory; Mann, J John; Parsey, Ramin V
<x xml:space="preserve">Abstract</x> Objectives Bipolar disorder (BD) is a psychiatric disorder with high morbidity and mortality that cannot be distinguished from major depressive disorder (MDD) until the first manic episode. A biomarker able to differentiate BD and MDD could help clinicians avoid risks of treating BD with antidepressants without mood stabilizers. Methods Cortical thickness differences were assessed using magnetic resonance imaging in BD depressed patients (n = 18), MDD depressed patients (n = 56), and healthy volunteers (HVs) (n = 54). A general linear model identified clusters of cortical thickness difference between diagnostic groups. Results Compared to the HV group, the BD group had decreased cortical thickness in six regions, after controlling for age and sex, located within the frontal and parietal lobes, and the posterior cingulate cortex. Mean cortical thickness changes in clusters ranged from 7.6 to 9.6% (cluster‐wise p‐values from 1.0 e‐4 to 0.037). When compared to MDD, three clusters of lower cortical thickness in BD were identified that overlapped with clusters that differentiated the BD and HV groups. Mean cortical thickness changes in the clusters ranged from 7.5 to 8.2% (cluster‐wise p‐values from 1.0 e‐4 to 0.023). The difference in cortical thickness was more pronounced when the subgroup of subjects with bipolar I disorder (BD‐I) was compared to the MDD group. Conclusions Cortical thickness patterns were distinct between BD and MDD. These results are a step toward developing an imaging test to differentiate the two disorders.